Successful Pregnancy after Previous Uterine Rupture - Tiwari, Kenusha Devi; Karki, Aruna; Dangal, Ganesh; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin; Poudel, Rekha; Bajracharya, Nishma; Bharati, Sonu (Europasian Journal of Medical Sciences, 2020)
Uterine rupture is a rare and catastrophic incidence with high maternal and fetal morbidity rates. It is most commonly seen in the scarred uterus. The unscarred uterus is least susceptible to rupture with the incidence being 1 in 8000 deliveries. In the past, pregnancy after uterine rupture was not widely advised and patients underwent hysterectomy or tubal ligation but with the evolving practice, women are motivated for pregnancy which can be successful with proper obstetric care and emphasis on time and mode of delivery. Here we present a case of 31 years old female, gravida 2 para 1 living 0 with previous uterine rupture after medical induction of labor with stillbirth 4 years ago. She underwent emergency laparotomy with the repair. The patient spontaneously conceived and had close antenatal care throughout the pregnancy. The patient was admitted at 34 weeks of gestation and kept under close surveillance. Corticosteroid was administered. She underwent spontaneous labor at 37 weeks of gestation and emergency cesarean section was planned, delivered via a breech presentation to a live baby of 2.4 kg, APGAR score of 8/10, 9/10 at 1 and 5 minutes. DOI: https://doi.org/10.46405/ejms.v2i1.22